Life after prostate cancer diagnosis: protocol for a UK-wide patient-reported outcomes study. Issue 12 (7th December 2016) - Downing, Amy; Wright, Penny; Wagland, Richard; Watson, Eila; Kearney, Therese; Mottram, Rebecca; Allen, Majorie; Cairnduff, Victoria; McSorley, Oonagh; Butcher, Hugh; Hounsome, Luke; Donnelly, Conan; et al.
Abstract : Background: Prostate cancer and its treatment may impact physically, psychologically and socially; affecting the health-related quality of life of men and their partners/spouses. The Life After Prostate Cancer Diagnosis (LAPCD) study is a UK-wide patient-reported outcomes study which will generate information to improve the health and well-being of men with prostate cancer. Methods and analysis: Postal surveys will be sent to prostate cancer survivors (18–42 months postdiagnosis) in all 4 UK countries (n=∼70 000). Eligible men will be identified and/or verified through cancer registration systems. Men will be surveyed twice, 12 months apart, to explore changes in outcomes over time. Second, separate cohorts will be surveyed once and the design will include evaluation of the acceptability of online survey tools. A comprehensive patient-reported outcome measure has been developed using generic and specific instruments with proven psychometric properties and relevance in national and international studies. The outcome data will be linked with administrative health data (eg, treatment information from hospital data). To ensure detailed understanding of issues of importance, qualitative interviews will be undertaken with a sample of men who complete the survey across the UK (n=∼150) along with a small number of partners/spouses (n=∼30). Ethics and dissemination: The study has received the following approvals: Newcastle and North Tyneside 1 Research Ethics Committee (15/NE/0036), Health Research Authority Confidentiality Advisory Group (15/CAG/0110), NHS Scotland Public Benefit and Privacy Panel (0516-0364), Office of Research Ethics Northern Ireland (16/NI/0073) and NHS R&D approval from Wales, Scotland and Northern Ireland. Using traditional and innovative methods, the results will be made available to men and their partners/spouses, the funders, the NHS, social care, voluntary sector organisations and other researchers.